Stability trend, weak bonding, and magnetic properties of the Al‐ and Si‐containing ternary‐layered borides MAB phases. Issue 2 (8th October 2022) - Qi, Xinxin; He, Xiaodong; Yin, Weilong; Song, Guangping; Zheng, Yongting; Bai, Yuelei
Abstract: With first‐principles calculations, a global screening was conducted for the Al‐ and Si‐containing MAB phases by considering their stability, damage tolerance, and magnetic properties, of much interest, where these predicted results are in good agreement with the available experimental ones. By examining the thermodynamics competing with all the experimentally identified phases and lattice dynamics, 29 stable MAB phases are predicted in total. Moreover, the Si‐containing MAB phases are much fewer than the Al‐containing ones, except for the 512 phases. Using the "bond stiffness" model, the strongest covalent bonding is formed between B and M/B atoms while the weakest bonding is formed between M/B and A atoms. For most Al‐containing MAB phases except 512‐type, the ratio of bond stiffness of weakest M‐Al or Al‐Al bonds to the strongest M‐B bonds ( k min / k max ) falls into the range of 1/3–1/2, indicating their high damage tolerance. But this is not true for the Si‐containing ones, with the k min / k max greater than 1/2 and strong M‐Si bonds. Furthermore, all the Fe/Mn/Co‐containing MAB phases are screened to be magnetic, with the accurately estimated Curie temperature ( T C ) and magnetic moment, where Fe2 AlB2 and Mn2 AlB2 have T C around room temperature, contributing to the future design of magnetic MAB phases for potential applications, such as the magnetic refrigeration and two‐dimensional MBenes.